Development and characterization of microsatellite primers for Chamaecyparis obtusa (Cupressaceae)(1) - Kim, Young Mi (Appl Plant Sci, 2016)
PREMISE OF THE STUDY: Although several microsatellite markers of Chamaecyparis obtusa (Cupressaceae) have been reported in previous studies, we newly developed and evaluated polymorphic microsatellite markers of C. obtusa, an economically important species in Korea as a major forestation tree species, for further genetic studies. METHODS AND RESULTS: Microsatellite-enrichment libraries were constructed according to the selective hybridization method. From this output, we obtained 10 polymorphic and five monomorphic microsatellite markers for C. obtusa. Five of these developed markers were successfully amplified for C. pisifera, a related species. CONCLUSIONS: These microsatellite markers can be valuable tools for further genetic studies of C. obtusa, and gathered genetic information may be useful for breeding program management.